School knowledge: gender imaginary of the educational community of the institution tri-ethnic Yaaliakeisy (Orinoquia, 2021)
The social manifestations that show gender inequality, are present in allareas of human activity, are more visible in those rural environments, whereindigenous settlements survive, whose social relations with other cultures aremarked by gender imaginations that are They express precisely, in the setting of this research, carried out during 2017, atthe Trietnica Yaaliakeisy Educational Institution of the Municipality of Puerto López, departmentof Meta, a pedagogical environment where members of the peasant community and the Achagua, Sikuani, ethnic groups coexist. Piapoco andKubeo. The research objective is to identify the gender manifestations of teachers and students of this institution, to address the knowledge ofhow expressions that demonstrate the existence of social imaginaries related to the roles of women and men are communicated. In methodologicalterms, the qualitative ethnographic approach was chosen, applying direct observation techniques, information gathering through semi-structuredinterviews and field work with focus groups; systematization of the information through the categorization and subcategorization of the data andits examination with the content analysis methodology. The results of the research show that there are gender roles through which themembersof this community perceive the condition of women as fragility and that of men as power. It is concluded that in this scenario the conditions ofinequality are maintained that, due to nurtured traditions, from ethnic cultural expressions, privilege the roles of the masculine over thefeminine.Faced with this panorama, it is necessary to sensitize the communities by transforming thoughts of submission and domination, into imaginarywhere representations of equality between genders persist, ensuring that the new generations, in these communities, train their daughters and sonswith human values based on gender equality.
Keywords: social imaginaries; gender equality; ethnic education